2017
DOI: 10.1097/shk.0000000000000907
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Heparan Sulfate Fragments Attenuate Histone-Induced Lung Injury Independently of Histone Binding

Abstract: Extracellular histones are cationic damage-associated molecular pattern molecules capable of directly inducing cellular injury via charge-mediated interactions with plasma membranes. Accordingly, histones released into the plasma during critical illness are known to contribute to the onset and propagation of lung injury. Vascular injury (with consequent degradation of the endothelial glycocalyx) simultaneously releases anionic heparan sulfate fragments (hexa- to octasaccharides in size) into the plasma. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 24 publications
0
25
1
Order By: Relevance
“…As noted, unfractionated heparin is composed of a mixture of distinct biologically derived (i.e., porcine intestinal mucosae) heparan sulfate polysaccharides, which on balance not only is enriched in a pentasaccharide sequence necessary for AT3 activation (and thus anticoagulation) but also displays a wide variety of other sulfation sequences. These non-anticoagulant sulfation sequences allow heparin binding to various growth factors, potentially exerting both organ-protective ( 46 , 49 ) and organ-harmful ( 14 , 20 ) effects.…”
Section: Potential Adverse and Off-target Effects Of Heparin Therapymentioning
confidence: 99%
“…As noted, unfractionated heparin is composed of a mixture of distinct biologically derived (i.e., porcine intestinal mucosae) heparan sulfate polysaccharides, which on balance not only is enriched in a pentasaccharide sequence necessary for AT3 activation (and thus anticoagulation) but also displays a wide variety of other sulfation sequences. These non-anticoagulant sulfation sequences allow heparin binding to various growth factors, potentially exerting both organ-protective ( 46 , 49 ) and organ-harmful ( 14 , 20 ) effects.…”
Section: Potential Adverse and Off-target Effects Of Heparin Therapymentioning
confidence: 99%
“…Recent studies have reported that NETs are present in tissues and the circulation of COVID-19 patients [75] , suggesting that their cytotoxicity contributes to disease. Negatively charged heparin and, desulphated heparin oligosaccharides has been demonstrated to neutralise the cytotoxic effect of positively charged histones, thereby potentially reducing organ damage [79] , [80] , [81] . In summary, heparin/LMWH may neutralise the inflammatory and cytotoxic effects of extracellular histones in COVID-19.…”
Section: Potential Beneficial Non-anticoagulant Effects Of Heparin/lmmentioning
confidence: 99%
“…These disaccharides may be sulfated at specific sites (including the 2-O position of iduronic acid and/or the 6-O or N position of glucosamine), imparting a domain patterning of negative charge. During sepsis, the glycocalyx is fragmented, releasing heparan sulfate hexa-and octasaccharides into the bloodstream (14)(15)(16). These fragments have the capacity to interact with soluble proteins (such as growth factors) with remarkable specificity through sulfation-based electrostatic interactions, influencing a variety of homeostatic and/or pathologic signaling pathways (17).…”
Section: Introductionmentioning
confidence: 99%